ITIL v3 and Van Grembergen Framework for System Transition Process - Wulandari, Desi; Buliali, Joko Lianto (IPTEK Journal of Proceedings Series, 2019)
Recently, PT XYZ replaced their old ERP system into the Microsoft Dynamics AX 365. PT XYZ has twenty branch offices. The system transition process uses direct conversion and pilot conversion models. This study reports on how ITIL v3 and Van Grembergen Framework can work together in developing guidelines for system transition processes. This study was conducted by mapping the organizational structure, processes, and relational mechanisms in accordance with the Van Grembergen framework. The results obtained from this mapping will be used as material for consideration for the preparation of governance using the ITIL v3 framework. This research will only use the Service Transition domain on ITIL. The questionnaire was taken in part from the template issued by UCISA. As a result of the study, we present that ITIL v3 and Van Grembergen are able to be used to rebuild structures, processes, and relational mechanisms after the system transition process is done. And also to improve how to do the next transition process in another branch offices. Organizations must adapt and adapt to changes that means, Organizations cannot only carry out practices that have been done and hoped for get success like what happened in the past, because the practices in the past that have been done may not be valid now because the environment has changed. Therefore, in this case if organizations wants to achieve and gain a competitive advantage, it must focus and make changes to the goal strategic, having a far-sighted future